An Empirical Research on Influence of Job Satisfaction and Marital Satisfaction on Teachers’ Anomic Behavior - Xiangqian Wei (Forest Chemicals Review, 2021)
In order to study the relationship between job satisfaction, marital satisfaction and teachers’ anomic behavior, 512 teachers in primary and secondary schools were surveyed by questionnaire. The results show that: (1) job satisfaction is significantly positively correlated with marital satisfaction; (2) both job satisfaction and marital satisfaction are negatively correlated with three kinds of teachers’ anomie: emotional anomic behavior, professional ethics anomic behavior, and value-oriented anomic behavior; (3) marital satisfaction plays a completely mediating role in the influence of job satisfaction on the three teachers’ anomic behaviors, respectively. Conclusion: Marital satisfaction plays a completely mediating role in the influence of job satisfaction on teachers’ anomic behavior. It is of great theoretical and practical significance to pay attention to the impact of work-family relationship on teachers’ anomic behavior.